Entre especialização flexível e precarização do trabalho: um estudo de caso, a FATEC Araraquara - Romualdo, Taíse de Souza (2024)
This master's research is conducted by the following question: does the adoption of new forms of functional work organization in Brazilian technological higher education institutions correspond to an innovation, called flexible specialization, or is it a strategy of precarious work? To address this challenge, this work began with a survey, systematization and assessment of the theses on flexible specialization (in the broad context of the Industrial Revolution and the effects of toyotism) and on the recurring theme of precarious work. In the case of the reception of flexible specialization in Brazil, special attention was paid to its host in the 1990s, in a scenario of neoliberal policies and within the scope of the State Administrative Reform, with subsequent highlights of its assimilation in the field of higher education and, in particular, without a superior technological segment. The literature argued that flexible specialization, extremely important in the productive world, can lead to precarious work, when associated with the intensification of human labor. To make it possible to examine this possibility in Brazilian technological education, it was chosen for a case study, analyzing the implementation of FATEC Araraquara, a teaching unit at Centro Paula Souza, whose creation is aligned with the process of expanding technological higher education in the state of São Paulo, as well as the moment when the ethos of public management was inclined towards the routines and language of Management Reform and innovations in work management. The case analysis took into account the guidelines and the initial project, the unit's implementation process, the strategy for occupying technical-administrative loads, the relationship between the number of courses, students, teachers, demands of academic-administrative activity, in comparison with the size of the planned and concrete technical-administrative staff and, finally, with the profile of the work carried out by the workers. In the end, strategies of precarious work were found in the scenario.